FORMATION OF ECOLOGICAL CULTURE OF THE FUTURE ECOLOGIST IN THE PROCESS OF VOCATIONAL TRAINING IN COLLEGES AS A PEDAGOGICAL PROBLEM - Пузырь, Таисия; Павлюк, Сергей (SWorldJournal, 2021)
The article is devoted to the problem of ecological education and greening in ensuring the formation of ecological culture. It has been established that ecological-professional training of ecologists should be carried out in stages, provided ecological-p